2012
DOI: 10.1186/1756-0500-5-177
|View full text |Cite
|
Sign up to set email alerts
|

Congenital malformations among newborns admitted in the neonatal unit of a tertiary hospital in Enugu, South-East Nigeria - a retrospective study

Abstract: BackgroundCongenital abnormalities are not uncommon among newborns and contribute to neonatal and infant morbidity and mortality. The prevalence and pattern of presentation vary from place to place. Many a time the exact etiology is unknown but genetic and environmental factors tend to be implicated.MethodsThe objective of this study was to determine the prevalence of congenital malformations among newborns admitted in a tertiary hospital in Enugu, the nature of these abnormalities and the outcome/prognosis. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
66
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(104 citation statements)
references
References 6 publications
10
66
3
2
Order By: Relevance
“…However, in Europe, a perinatal death of 2.0% in the form of stillbirths or fetal deaths and neonatal deaths (2.5%) in the first week of life are attributed to congenital anomaly . In Nigeria, available data on congenital malformations are mostly from hospital‐based studies . Abbey et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in Europe, a perinatal death of 2.0% in the form of stillbirths or fetal deaths and neonatal deaths (2.5%) in the first week of life are attributed to congenital anomaly . In Nigeria, available data on congenital malformations are mostly from hospital‐based studies . Abbey et al .…”
Section: Introductionmentioning
confidence: 99%
“…in a descriptive retrospective cross‐sectional study conducted in a Nigerian teaching hospital reported a prevalence of 20.73 cases per 1000 live births, with the frequency in unbooked maternities significantly higher than the booked. Also, Obu et al . in a cross‐sectional retrospective review of medical records in a tertiary hospital in south‐eastern part of Nigeria reported a prevalence of 2.8%.…”
Section: Introductionmentioning
confidence: 99%
“…Herbert A Obu et al (2012) study revealed that, surgical birth defects are common Congenital anomalies (2.8%) which comprised of neural tube defect, ano-rectal malformations, cleft lip/cleft palate, limb abnormalities, omphalocoele, umbilical hernia, and dysmorphism accompanying with various Congenital annomalies 15 . This findings is similar to our study.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] The main cause of NTDs are abnormalities that occur during neurulation, which should be complete by 4 weeks postconception [8]. An estimated 1 in 1000 infants are born with a neural tube defect (NTD) annually in the United States [9], and more are spontaneously aborted or electively terminated.…”
Section: Wisam Abdullah Jasim and Hussein Imran Mousamentioning
confidence: 99%